Peter Sloterdijk: Experiments with oneself, voluntary intoxication tests and psychoimmune constitution of human nature - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2013)
We inquire about the poisoning, in a comprehensive program to experiment with one’s body, a method that finds its basis in the idea of romantic medicine where, according to Sloterdijk, the dose effects in the healthy and the sick were reflected specular manner. This is where an ambitious originates semiotics of pharmacological medication, not only endomorfinismo of speculation, but quimioéticos endocrine mechanisms. Sloterdijk refers to a process of voluntary intoxication in reference to the creator of homeopathy, Samuel Hahnemann, as inventor of a micropolitics of subjectivity. In the same way that the homeopath, as Hahnemann himself must intoxicated before giving any advice, political theorist must be willing to risk their identity in practice. Sloterdijk referring to such "experiments with oneself" and not think of an experiment in vivisection own flesh, nor romantic psychosis in psychoanalysis, but rather refers to a phenomenon belonging to the history of modern medicine, homeopathic movement, which goes back over two hundred years and whose effectiveness is verified with proposed therapeutic-adequate medical treat-able modern neurosis. It examines and discusses the unorthodox belief that the physician would be required to intoxicate himself with all that he was later to prescribe to patients. This reflection should experiment with the concept of self: who wants to be a doctor needs to be guinea pig previously, this is to be your own Indies pigs. The author is valuable and useful that is contaminated with the materials he works with, high toxic substances, this approach has not changed. Kafka, Musil, Broch, Burroughs all great twentieth century masters are also dangerous thought.